Revisiting the Legacy: The Ongoing Discourse on Ḥadīth of Ghadīr Khumm in Shiʻa Studies - Bahary, Ansor (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
The study of the hadith of Ghadīr Khumm has long been at the center of the Sunni-Shiʻa polemic. While previous research primarily focused on analyzing the sanad (chain of transmission) and matan (text), contemporary Shiʻa scholarship has increasingly employed it as a tool to continuously reinforce the doctrine of imāmah and counter Sunni epistemic dominance. This study examines how the hadith of Ghadīr Khumm is utilized in Shiʻa academic discourse by exploring the extent to which the polemic surrounding this hadith has evolved beyond mere authentication and how it functions in response to Sunni historiography. The findings indicate that, although many Sunni sources acknowledge the authenticity of the hadith of Ghadīr Khumm, stark differences in interpretation have led Shiʻa scholars to continue engaging with this hadith academically. This ongoing engagement is driven by the perception that the dissemination of Sunni perspectives remains a dominant force that must be challenged. Recent trends reveal that academic studies are increasingly directed toward integrating hadith interpretation into civilizational narratives as a response to marginalization. However, despite appearing innovative, the underlying argumentative patterns largely follow established precedents. This study opens avenues for further research into how hadith texts hold strong foundational value, ensuring their continued role as primary references in asserting theological legitimacy and shaping the identity of religious sectarian communities within Islam. Keywords: Hadith of Ghadīr Khumm, Sunni-Shiʻa polemic, discourse defense